Literature Review of Nature of Science and Explicit-Reflective Instruction: A Strategy Design in Scientific Literacy - Enik Setiyawati; Sutopo; Susriyati Mahanal; Lia Yuliati; Nataria Wahyuning Subayani (Indonesia Approach Education, 2024)
This study was conducted to synthesize the literature on the Nature of Science (NOS) and explicit-reflective instruction and find implications for a strategy design in scientific literacy. The main contribution of this research is the in-depth analysis of the selected articles to find aspects of NOS that are important for elementary school students as a bridge to achieving scientific literacy. This study used the literature review method with four stages: identifying research objectives, identifying and selecting relevant studies, mapping data, and compiling, summarizing, and reporting results. The source of the review was 25 articles that met the exclusion and inclusion criteria in the last 10 years. The presentation of results was done descriptively by paying attention to the full text of the 25 articles. This study revealed that empirically based, tentative, observations and inferences, and imagination and creativity are general aspects of NOS that are important for elementary school students to access as a bridge to scientific literacy. The implications of these findings suggest a strategy designed to provide many opportunities for teachers and students to use content and learning contexts with three phases of reflection called the reflective before-in-on strategy.